Association between traffic-related air pollution and risk of outpatient visits for dry eye disease in a megacity along the subtropical coast in South China - Fan Cao; Yue Chen; Yan-Chao Gui; Zi-Yue Fu; Zheng Lyu; Kou Liu; Li-Ming Tao; Zhi-Fan Chen; Hai-Feng Pan; Zheng-Xuan Jiang; Qian-Li Meng (BMC Public Health)
Abstract Background Traffic-related air pollution especially in highly socioeconomically developed megacity is usually considered as a severe problem leading to inevitable adverse health outcomes. This study aimed to investigate the associations between traffic-related air pollutants with risk of dry eye disease (DED) outpatient visits in a megacity (Guangzhou) along the subtropical coast in South China. Methods Daily data on DED outpatient visits and environmental variables from 1 January 2014 to 31 December 2020 in Guangzhou were obtained. A time-series study using a quasi-Poisson generalized linear model (GLM) combined with distributed lag non-linear model (DLNM) was adopted. Subgroup analyses stratified by age, gender, and season were conducted. Results Totally, 27, 828 DED cases were identified during the study period including 2557 days. Daily number of outpatient visits for DED ranged from 0 to 41. An increase of 10 μg/m3 in PM2.5, NO2 and SO2 concentration was associated with 3.1%, 5.9% and 17.4% increase in the risk of DED outpatient visits, respectively (RRPM2.5 = 1.031, 95%CI: 1.004–1.059, lag 0–11 day; RRNO2 = 1.059, 95% CI: 1.027–1.092, lag0-14 day; RRSO2 = 1.174, 95% CI: 1.036–1.330, lag0-13 day). Subgroup analyses indicated that the effects of PM2.5 exposure on the risk of DED outpatient visits remained significant in aged < 60 years (RR max = 1.008, 95% CI: 1.003–1.013, lag0 day) and the effects of SO2 exposure on the DED outpatient visits risk remained significant in the females (RR max = 1.025, 95% CI: 1.006–1.044, lag0 day). The associations of PM2.5 (RR = 1.010, 95% CI: 1.003–1.016, lag0 day) and SO2 (RR = 1.030, 95% CI: 1.003–1.058, lag14 day) exposure with DED outpatient visits risk remained significant in warm seasons, whereas NO2 (RR = 1.006, 95% CI: 1.002–1.009, lag14 day) exposure was significantly associated with DED outpatient visits in cold seasons. The associations of PM2.5 (first visit, RR = 1.006, 95% CI: 1.001–1.011, lag0 day; re-visit, RR = 1.002, 95% CI: 1.000–1.005, lag6 day), NO2 (first visit, RR = 1.006, 95% CI: 1.001–1.012, lag0 day; re-visit, RR = 1.007, 95% CI: 1.002–1.012, lag0 day), and SO2 (first visit, RR = 1.023, 95% CI: 1.002–1.044, lag0 day; re-visit, RR = 1.023, 95% CI: 1.000–1.045, lag0 day) exposure with risk of DED outpatient visits were significant for both first- and re-visits. Conclusions Our study revealed that short-term exposure to PM2.5, NO2 and SO2 were positively associated with risk of DED outpatient visits, especially for the youngers, females and during warm seasons, providing evidence for making public health policy to improve life quality in developed megacity.